1998
DOI: 10.1111/j.1708-8305.1998.tb00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Melatonin on Driving Performance

Abstract: The overall result of the computer test battery showed no objective adverse impact of melatonin on driving performance. However, due to the increased subjective sleepiness after administration of this hormone, caution should be exercised when driving under the influence of melatonin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 28 publications
1
15
0
1
Order By: Relevance
“…However, neurobehavioral impairments produced by daytime melatonin appeared less pronounced than those induced by a benzodiazepine (Rogers et al, 2003). These results are consistent with the Suhner's ones (Suhner et al, 1998), which showed no effect of melatonin (5 mg) on driving skill assessed by a driving computer test battery 90 min after a daytime administration. Altogether, these results suggest that PR-M administered at bedtime is devoid of deleterious effects on cognitive performances and driving abilities of elderly subjects even early after its administration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, neurobehavioral impairments produced by daytime melatonin appeared less pronounced than those induced by a benzodiazepine (Rogers et al, 2003). These results are consistent with the Suhner's ones (Suhner et al, 1998), which showed no effect of melatonin (5 mg) on driving skill assessed by a driving computer test battery 90 min after a daytime administration. Altogether, these results suggest that PR-M administered at bedtime is devoid of deleterious effects on cognitive performances and driving abilities of elderly subjects even early after its administration.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies reported alterations of alertness and performances by acute melatonin when administered during daytime (Atkinson et al, 2005;Cajochen et al, 1996;Dollins et al, 1993;Graw et al, 2001;Lieberman et al, 1984;Neville and McNaughton, 1986;Rogers et al, 1998) but not when administered during late afternoon or at bedtime in young and middle-aged (20-57 years) healthy volunteers (Paul et al, 2003;Stone et al, 2000;Suhner et al, 1998;Wynn and Arendt, 1988). Furthermore, melatonin administered nightly for 4 weeks improved certain aspects of cognition in healthy elderly subjects (Peck et al, 2004).…”
Section: Introductionmentioning
confidence: 91%
“…These data mimic previous studies (Dollins et al 1993; Dollins et al 1994; Rogers et al 2003), and further emphasize the need to caution those who take melatonin in the afternoon or evening not to drive or engage in an activity that requires full alertness, even if relatively low doses are taken. Although one noteworthy study did not find an adverse effect on driving performance after ingesting 5 mg of melatonin (Suhner et al 1998), a significant increase in subjective sleepiness emerged, which led the authors to similarly conclude that caution should be used when driving after taking melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…Suhner et al. found that selective attention in a signal‐detection test was affected in humans and that their subjective sleepiness was increased by daytime administration of melatonin. Graw et al.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, recent research has suggested that melatonin is a potential candidate for additive therapy of cancer, neurodegenerative, and mental disorders requiring administration during the waking period [3,[7][8][9][10]. Because melatonin is currently used during the rest phase as a hypnotic, few data address the cognitive effects of melatonin on the activity phase [9,11]. Suhner et al [9] found that selective attention in a signal-detection test was affected in humans and that their subjective sleepiness was increased by daytime administration of melatonin.…”
Section: Introductionmentioning
confidence: 99%